2013
DOI: 10.1155/2013/869418
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Condyle Fracture of the Humerus in Children Treated with Bioabsorbable Materials

Abstract: The aim of this study was to compare clinical and radiological outcome of lateral condyle fracture of the elbow in children treated with bioabsorbable or metallic material. From January 2008 to December 2009, 16 children with similar fractures and ages were grouped according to the fixation material used. Children were seen at 3, 6, and 12 months and more than 4 years (mean 51.8 months) postoperatively. The clinical results were compared using the Mayo Elbow Performance Score (MEPS). Radiographic studies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…Lateral humeral condyle fractures are a common injury in children [1]. They account for between 12 and 20% of all elbow fractures [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Lateral humeral condyle fractures are a common injury in children [1]. They account for between 12 and 20% of all elbow fractures [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…Of the ten studies, eight reported outcomes of K-wire fixation, [19][20][21][22][23][24][25][26][27][28] four reported the outcomes of screw fixation, 21,27,20,24 one reported outcomes of fixation with bioabsorbable materials 19 and one of screw-wire fixation. 28 In addition, three studies looked exclusively at closed reduction.…”
Section: Resultsmentioning
confidence: 99%
“…Primary Outcome -Functional Outcomes K-wire fixation had excellent functional outcomes in 52% 28 to 100% 19 of patients. Screw fixation had excellent functional outcomes in 89% 27 to 100% 20 of patients.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12][13] Smooth Kirschner wires (K-wire) are the most commonly used metallic implants for fixation of the fracture. 8,14 But this fixation requires an additional immobilization with a plaster splint or a cast for four to six weeks. Few recently published reports suggest the use of cannulated cancellous (CC) screws for fracture fixation as it provides compression at the fracture site and is a more stable construct.…”
Section: Comparison Of Kirschner Wires and Cannulated Screw Internal mentioning
confidence: 99%